The prevalence of insulin resistance in patients with Î² -thalassemia major at Cipto Mangunkusumo Hospital - Caroline Mulawi; Bambang Tridjaja; Maria Abdulsalam; Zakiudin Munasir (Indonesian Pediatric Society, 2003)
Background Diabetes mellitus is a common complication in pa-tients with thalassemia major. Iron overload plays an important roleby damaging the pancreatic Î²-cell and the liver cell, with the con-sequences of insulin deficiency and insulin resistance. Family his-tory of diabetes mellitus is one of the critical factors for the devel-opment of glucose metabolism derangement. However, the patho-genesis of glucose metabolism derangement remains unclear.Objective To evaluate the prevalence of impaired glucose toler-ance, diabetes mellitus, and insulin resistance in patients with Î²-thalassemia major treated in the Thalassemia Outpatient Clinic,Department of Child Health, Cipto Mangunkusumo Hospital,Jakarta.Methods This was a descriptive cross sectional study conductedin May 2002. Forty-eight subjects aged 10 to 18 years, grouped bytotal volume of transfusions and family history of diabetes mellitus,underwent an oral glucose tolerance test (OGTT), serum transfer-rin saturation, and insulin level examinations. Insulin resistancewas calculated from fasting plasma glucose and insulin concen-trations using the homeostasis model assessment (HOMA).Results One of 48 patients (2%) had impaired glucose toleranceat the age of 17 years. Diabetes mellitus occurred in three of 48patients (6%) at the age of 15.5 years in one patient and 18 yearsin two patients. Family history of diabetes mellitus was found in 2patients with diabetes mellitus and in the only one with impairedglucose tolerance. Insulin resistance was not detected in this study.Conclusion The prevalence of glucose metabolism derangementin patients with thalassemia major was low. No insulin resistancewas found in this study